2014
DOI: 10.1136/bcr-2014-203923
|View full text |Cite
|
Sign up to set email alerts
|

Cat eye syndrome

Abstract: A full-term female baby, a product of non-consanguineous marriage, was born at 37 weeks of gestation with a birth weight of 2.08 kg. Antenatal scan at 31 weeks revealed complex congenital heart disease with a hypoplastic right ventricle, pulmonary atresia and an intact septum. Immediately after birth, the infant was shifted to the nursery and was started on intravenous fluids and infusion prostaglandin E1 (Alprostidil). On examination, she had microcephaly, periorbital puffiness, a long philtrum, a broad nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 10 publications
(4 reference statements)
0
25
0
Order By: Relevance
“…The name is derived from the ophthalmologic findings of bilateral vertical iridal and choroidal colobomas, which give the appearance of cat eyes. 1,2 CES, also known as Schmid-Fraccaro syndrome, is a rare genetic disorder caused by duplication or triplication of the proximal long (q)arm of chromosome 22, including regions proximal to the common region deleted in patients with DiGeorge and Velocardiofacial syndromes. 1,3,4 The most common cause of this disorder is the presence of a supernumerary dicentric chromosome 22, often observed in mosaic form.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The name is derived from the ophthalmologic findings of bilateral vertical iridal and choroidal colobomas, which give the appearance of cat eyes. 1,2 CES, also known as Schmid-Fraccaro syndrome, is a rare genetic disorder caused by duplication or triplication of the proximal long (q)arm of chromosome 22, including regions proximal to the common region deleted in patients with DiGeorge and Velocardiofacial syndromes. 1,3,4 The most common cause of this disorder is the presence of a supernumerary dicentric chromosome 22, often observed in mosaic form.…”
Section: Introductionmentioning
confidence: 99%
“…This extra chromosome is typically comprised of two "mirror-image" copies of the satellite, short arm, and centromeric region of chromosome 22, including a portion of the long arm of chromosome 22 with a "hinge point" at 22q11.21. 1,2 The syndrome affects approximately 1 in every 50,000 to 150,000 live births. 2,4 Phenotypic variance is common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The TBX1 gene encoding an important transcriptional factor implicated in numerous developmental processes and contained in the DGS/VCFS region has been tentatively correlated with the occurrence of polydactyly. 7 However, the supernumerary marker in our patient did not include TBX1. A few research results have suggested an important role of other unknown genes or complex interactions between amplified regions in the pathogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…We show that Cecr2 homozygotes can have post-and pre-axial polydactyly, of which only pre-axial involves cartilage or bone. Only one relevant case of CES has been reported with right upper limb post-axial polydactyly 24 . A more common skeletal defect in CES is scoliosis 2,3 .…”
Section: Discussionmentioning
confidence: 99%